F aktor-Faktor Yang Berhubungan dengan Penggunaan Sarana Jamban Keluarga Di Desa Dadap Kecamatan Juntinyuat Kabupaten Indramayu: (Factors Associated with the Provision And Use of Means of Family Latrines In the Village Dadap District Juntinyuat Indramayu - Sudirman; Hairil Akbar (Universitas Widya Gama Mahakam Samarinda, 2021)
Background Making latrines is a human effort to improve health by creating a healthy environment in which to live. In making latrines, as much as possible, care must be taken so that they do not cause unpleasant odors. Objectives This study to see the relationship between the level of education, behavior, and income of the community and the use of family toilet facilities in Dadap Village, Juntinyuat District, Indramayu Regency in 2018. Research Methods This research uses quantitative research with an analytic observational approach using the Cross-Sectional Study method. The population of this study was all heads of households in the village of Dadap with a sample size of 98 people. Result The statistical test (Chi-Square test) show the results that the level of education is p = 0.240> 0.05 indicates there is no relationship between education and the use of family latrines. Behavior p = 0.000 <0.05 indicates a relationship between behavior and the use of family latrines. Income p = 0.000 <0.05 indicates that there is a relationship between income and the use of family toilet facilities. Conclusion It can be concluded that the research results have no relationship between education and the use of family toilet facilities in Dadap Village, Juntinyuat District, Indramayu Regency. Behavior and income have a relationship with the use of family toilet facilities in Dadap Village, Juntinyuat District, Indramayu Regency. The need for increased education, to improve changes in people's behavior to create a clean and healthy life.